2017
DOI: 10.1111/his.13124
|View full text |Cite
|
Sign up to set email alerts
|

The mitosis‐specific marker phosphohistone‐H3 (PHH3) is an independent prognosticator in uterine smooth muscle tumours: an outcome‐based study

Abstract: PHH3 is useful in evaluation of the biological behaviour of USMTs, and may serve as a prognostic indicator for LMSs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 71 publications
(224 reference statements)
0
25
0
Order By: Relevance
“…Our histological values have some discrepancies from previous reports, probably because we used mean values to subgroup the cases while previous studies used different cutoff values, such as Youden index obtained from receiver operating characteristic analysis. 31 Collectively, our results should be perceived with caution and need to be validated in a larger cohort with detailed treatment and prognostic information.…”
Section: An Advantage Of Assessing Mitotic Figures Over Other Prognosticmentioning
confidence: 89%
See 2 more Smart Citations
“…Our histological values have some discrepancies from previous reports, probably because we used mean values to subgroup the cases while previous studies used different cutoff values, such as Youden index obtained from receiver operating characteristic analysis. 31 Collectively, our results should be perceived with caution and need to be validated in a larger cohort with detailed treatment and prognostic information.…”
Section: An Advantage Of Assessing Mitotic Figures Over Other Prognosticmentioning
confidence: 89%
“…The phosphorylated state of histone H3 (phosphohistone H3 [PHH3]) can only be identified during mitosis but not in interphase or apoptosis. Thus, the immunohistochemical expression of PHH3 can be a surrogate marker for mitotic figures in malignant tumors of various organs . In breast cancers, previous studies have found that PHH3 better predicts patient prognosis, compared to other markers including mitotic figures in hematoxylin and eosin (H&E)–stained slides and Ki67 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of the 19 articles were extracted and are summarized in Table 1 . The patients were from People’s Republic of China, 8 , 13 , 14 Korea, 15 Norway, 10 , 16 18 India, 19 Germany, 9 , 20 the United Kingdom, 21 , 22 the United States of America, 11 , 23 New Zealand, 24 Sweden, 25 Australia, 26 and Italy. 27 The types of carcinoma included glioma, neuroblastoma, gastric cancer, gastrointestinal stromal tumor, Merkel cell carcinoma, cutaneous melanoma, uterine smooth muscle tumor, endometrial cancer, adrenocortical carcinoma, prostate cancer, and breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Recognition of this common pattern is important to prevent overdiagnosis of STUMP/atypical smooth muscle tumour. The search for new biomarkers for uterine smooth muscle tumour is necessary …”
Section: Discussionmentioning
confidence: 99%